2020
DOI: 10.1007/s13566-020-00419-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of nivolumab in combination with prior or concurrent radiation therapy in hepatocellular carcinoma

Abstract: Objectives Nivolumab has been demonstrated to be effective for the treatment of unresectable hepatocellular carcinoma (HCC). While many patients may additionally benefit from radiation therapy (RT), the toxicity of combination nivolumab and RT is unknown. Methods Patients who underwent liver-directed RT prior to or concurrent with nivolumab for HCC at our institution were reviewed. Toxicity was assessed by Common Terminology Criteria for Adverse Effects v5.0 criteria until disease progression, change in system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Since no data was found on combined treatment with locoregional and immunotherapy in the setting of transplantation, data outside transplant setting was assessed. In this context, a total of 450 references were identified, whereas 14 were eventually included for further review (Supplementary Table S10) [105][106][107][108][109][110][111][112][113][114][115][116][117][118][119]. Two of these were systematic reviews and meta-analyses [105,106].…”
Section: Strength Of Recommendation: N/amentioning
confidence: 99%
See 1 more Smart Citation
“…Since no data was found on combined treatment with locoregional and immunotherapy in the setting of transplantation, data outside transplant setting was assessed. In this context, a total of 450 references were identified, whereas 14 were eventually included for further review (Supplementary Table S10) [105][106][107][108][109][110][111][112][113][114][115][116][117][118][119]. Two of these were systematic reviews and meta-analyses [105,106].…”
Section: Strength Of Recommendation: N/amentioning
confidence: 99%
“…Finally, of the seven non-randomized retrospective studies, five focused on early-death or severe complications with none of the studies reporting any major complication or death associated with the treatment evaluated [108,[117][118][119][120]. In the remaining two retrospective studies safety was not reported [107,109]. Although these data provide valuable insight into the safety and long-term oncologic outcomes of combined treatments of locoregional therapy and immunotherapy in a non-transplant setting, they cannot be extrapolated to a transplant/waitlist-setting.…”
Section: Strength Of Recommendation: N/amentioning
confidence: 99%